Zagreb glavni kolodvor u urbanističkim planovima od 1865. godine do danas - Stjepan Kelčec-Suhovec (Promet - Traffic&Transportation, 1970)
The first railway line was introduced in Zagreb in 1862, while the Central Station was built in 1892. At the time of its construction the station was located to the south of the town outside the built-up urban area. For reasons of accelerated development of the urban area, undoubtedly supported by the railways as well, further continuing urban spread to the south and railway lines soon reached the point of confrontation, in particular the Central Station buildings and facilities for their location, size and level. The paper deals with different designs of the Central Station as anticipated in the urban area development plans over the period of past hundred years and the actual situation reported in practice.